Strategi Pengembangan Objek Wisata Pantai Tabanio di Desa Tabanio Kecamatan Takisung Kabupaten Tanah Laut di Era New Normal - Fathi, Muhammad; Rahmini, Noor (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to (1) determine the internal factors that are strengths and weaknesses in the development of Tabanio Beach tourism in Tanah Laut Regency, (2) find out external factors that are opportunities and threats in the development of Tabanio Beach tourism in Tanah Laut Regency and (3) strategies development of Tabanio Beach tourism object in Tanah Laut Regency. Seven respondents responded that they had an influence and played an essential role in developing Tabanio Beach tourism objects. The results of the survey show the condition of the Tabanio Beach tourist attraction in the New Normal Era; the resulting development strategy that is most appropriate to the situation is the S-O strategy (1) Improving and maintaining the quality of the natural beauty of the tourist attraction to make tourists comfortable with the cool air when visiting with family while holidaying. (2) Increasing Government support and the role of POKDARWIS (Tourism Awareness Group) in adding new tourist attractions at Tabanio Beach tourist attraction.